Profiles of Impulsivity in Problematic Internet Users and Cigarette Smokers - Liu, Su-Jiao; Lan, Yan; Wu, Lin; Yan, Wan-Sen (Frontiers in Psychology, 2019)
Problematic Internet use (PIU) has been gradually recognized as a mental health issue among adolescents and young students. PIU shows many similarities with substance use disorders, but the shared and distinct mechanisms underlying them are unclear. The purpose of the current study was to explore the relationships between impulsive traits and PIU as well as cigarette smoking behaviors among young adults. Two independent samples of university students (N1=1281, N2=1034, respectively) over three years were assessed with multiple measurements of impulsivity, including the Barratt Impulsiveness Scale-11 (BIS-11), the UPPSP Impulsive Behaviors Scale (UPPSP), and the Delay-discounting Test (DDT). Logistic regression models revealed that across the two independent samples, BIS-11 Attentional Impulsiveness was the common trait positively predicting both PIU and cigarette smoking. While BIS-11 Motor Impulsiveness as well as UPPSP Lack of Perseverance, Lack of Premeditation, and Negative Urgency were the typical traits linked to PIU as positive predictors, UPPSP Sensation Seeking was the unique trait linked to cigarette smoking as a positive predictor. These results suggested that specific dimensions of impulsivity might be concurrently implicated in PIU and cigarette smoking among young adults, putatively representing important trait marks for addictive behaviors.